Features of aspect marking in Singapore Mandarin - Khoo Yong Kang (Nanyang Technological University, 2020)
Variations in Singapore Mandarin are noted by many scholars and studies, though not all areas of these variations have been equally well-studied. Grammatical aspect is one of the areas that has received relatively little attention from scholarship on Singapore Mandarin; to date, there is still a lack of systematic studies that investigates the features of grammatical aspect marking in Singapore Mandarin. This thesis aims to fill this gap by conducting a corpus-based investigation on spoken Singapore Mandarin, focusing on the marked grammatical aspects that can be found in the variety. Aside from the more widely-discussed aspect markers in Mandarin, that is, the perfective 了 le, the currently-relevant-state 了 le, the experiential perfect 过 guò, and the continuous 着 zhe, this thesis also looks into markers that are very seldom discussed or not presumed to exist in Putonghua and other Mandarin varieties, such as 了 liǎo, 有 yǒu, and 住 zhù. There are three major discussions about the aspect markers of Singapore Mandarin. First, it is observed that the verb 了 liǎo can be used as an aspect marker denoting the perfective and the currently-relevant-state aspect in Singapore Mandarin, though it does differ from 了 le when it is used as a perfective aspect marker. In particular, it occurs consecutively with the currently-relevant-state 了 le, as in 了了 liǎo le at the end of a sentence or clause. An investigation of the construction shows that it may have roots in Chinese vernaculars such as Southern Min. Second, the morpheme 住 zhù may potentially be used as a continuous marker like 着 zhe, though it presents slightly different constraints in its use. For instance, it seems to occur more frequently with verbs that are compatible with the notion of ‘be firm’, likely because of its complemental functions. Unlike previous studies, this thesis does not treat 住 zhù as a ‘quasi-aspect marker’ because of this characteristic. Instead, 住 zhù is simply taken to be part of a zhù construction that can express both its complemental and its aspectual functions. Third, this thesis also attempts to clear up the interpretations put forth by previous researchers of 有 yǒu in yǒu constructions. The aspectuality of this marker has been disputed in many previous studies and approaches to interpreting them have been disorganized, often resulting in contradictory claims that cannot or are not yet resolved. Using Singapore Mandarin data, the current work suggests that 有 yǒu codes for an existential perfect aspect in Singapore Mandarin, a new category proposed in this thesis. This study also attempts to apply this interpretation to other varieties of Mandarin, such as Taiwan Mandarin and Hong Kong Mandarin, and Chinese vernaculars. Differences between the observations in the current study and in previous works are also reconciled where possible, in hopes of producing a more organized and less contradictory account of aspect marking in Singapore Mandarin, such that this thesis may become a stepping stone toward a deeper understanding of the variety, not just in terms of aspect marking, but in general terms as well.